A Case Report and Literature Review of Prostatic Tuberculosis Masquerading as Prostate Cancer: A Diagnostic Challenge in a Tuberculosis-Endemic Region - Yonathan William; Marto Sugiono; Patricia Diana Prasetiyo; Adelbertus Erico; Gilbert Sterling Octavius (Tropical Medicine and Infectious Disease)
A male in his 60s presented with a four-month history of dysuria and lower urinary tract symptoms (LUTS). He had a history of elevated PSA and benign prostatic hyperplasia (BPH), previously treated with transurethral resection of the prostate (TURP). Multiparametric MRI (MP-MRI) revealed a PI-RADS 5 lesion, raising suspicion of malignancy. However, histopathological analysis from MRI fusion-targeted biopsies confirmed tuberculous prostatitis. The patient was treated with antituberculosis drugs, resulting in symptomatic improvement and a significant PSA decline. This case highlights the diagnostic challenge of distinguishing tuberculous prostatitis from prostate cancer, particularly in tuberculosis-endemic regions. Our literature review reveals that patients with tuberculous prostatitis undergoing MRI are at least 50 years old, originate from endemic areas, and exhibit PI-RADS scores ranging from 2 to 5, indicating inter-rater variability. Histopathological confirmation remains essential in cases with ambiguous imaging and clinical findings.